2020
DOI: 10.1186/s13229-020-00330-9
|View full text |Cite
|
Sign up to set email alerts
|

SCN2A channelopathies in the autism spectrum of neuropsychiatric disorders: a role for pluripotent stem cells?

Abstract: Efforts to identify the causes of autism spectrum disorders have highlighted the importance of both genetics and environment, but the lack of human models for many of these disorders limits researchers' attempts to understand the mechanisms of disease and to develop new treatments. Induced pluripotent stem cells offer the opportunity to study specific genetic and environmental risk factors, but the heterogeneity of donor genetics may obscure important findings. Diseases associated with unusually high rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 108 publications
0
17
0
Order By: Relevance
“…The largest gene discovery effort to date identified approximately 102 genes highly associated with ASD [58]. Emerging from these large-scale genetic studies are "channelopathies" or dysfunction of various ion channels as causative factors in ASD pathogenesis [59][60][61][62][63][64][65][66]. A substantial number of these genes are of the Na V , Ca V , and potassium channel families, as well as HCN channels [66].…”
Section: Impaired Dendritic Excitability and Synaptic Integration In Nddsmentioning
confidence: 99%
“…The largest gene discovery effort to date identified approximately 102 genes highly associated with ASD [58]. Emerging from these large-scale genetic studies are "channelopathies" or dysfunction of various ion channels as causative factors in ASD pathogenesis [59][60][61][62][63][64][65][66]. A substantial number of these genes are of the Na V , Ca V , and potassium channel families, as well as HCN channels [66].…”
Section: Impaired Dendritic Excitability and Synaptic Integration In Nddsmentioning
confidence: 99%
“…That these peptidomimetics bind to both FGF14 and Nav1.6 is desirable in that it affords multiple mechanisms by which they could modulate the PPI between FGF14 and Nav1.6. In the case of the inhibitor (12), its disruption of the PPI between FGF14 and Nav1.6 could be conferred via direct binding to the FGF14 interaction site on the C-terminal tail of Nav1.6 or via binding to FGF14 and causing the protein to undergo a conformational change that makes it inaccessible to its native interaction site on the C-terminal tail of Nav1.6. Similarly, for the potentiator of FGF14:Nav1.6 complex assembly (19), its modulatory effects on the PPI could be conferred by both binding to the C-terminal tail of Nav1.6 that makes the FGF14 interaction site increasingly accessible to the regulatory protein, or, conversely, by binding to FGF14 and causing it to undergo a conformational change that affords it with increased accessibility to its interaction site on the C-terminal tail of Nav1.6.…”
Section: Fgf14mentioning
confidence: 99%
“…Heretofore, it had been shown that addition of a N-terminal benzoyl substituent (19) to tetrapeptide analogs produced an efficacious potentiator of FGF14:Nav1.6 complex assembly, whereas truncation to a tripeptide (12) yielded an inhibitor of the complex s assembly. Additionally, both 12 and 19 demonstrated promising protein:ligand binding interactions.…”
Section: Electrophysiological Evaluation Of Compounds 12 and 19mentioning
confidence: 99%
See 1 more Smart Citation
“…SCN2A has been reported as the gene with the strongest evidence for ASD-association based on exome analysis (12/4,109 cases) and second only to fragile X syndrome as a single-gene cause of ASD; recent reports suggest that SCN2A mutations may be associated with autism rates up to 50%. 8,[67][68][69] In these patients, symptoms are similar to those seen in more common forms of ASD, such as reduced social interaction and repetitive behaviors. Some patients also exhibit additional symptoms, such as intellectual disability and developmental delay, seizures, and symptoms of cerebellar dysfunction such as abnormal gait, clumsiness, and hypotonia.…”
Section: Intellectual Disability And/or Autism and Movement Disordersmentioning
confidence: 99%